Relationship of Childhood Idiopathic Nephrotic Syndrome with Asthma, Hypertension, Complement C3, Urinalysis - Roy, Ranjit Ranjan; Islam, Md Rafiqul; Matin, Abdul; Khan, Rita; Muinuddi, Golam; Rahman, Md Habibur; Hossain, Md Moazzam (Bangladesh Journal of Child Health, 2012)
A prospective observational study of 43 children with idiopathic nephrotic syndrome (INS) were selected randomly out of 480 children admitted with the disease at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2003 to January 2005. Aim of this study was to correlate the difference in frequency of atopic attack, hypertension, complement c3 level and urinalysis in different types of Idiopathic nephrotic syndrome. Result: Among 43 children with idiopathic nephrotic syndrome (INS), 24 children were steroid sensitive nephrotic syndrome (SSNS) and 19 children having steroid resistant nephrotic syndrome (SRNS) cases, of SSNS group 13 were infrequent relapse nephrotic syndrome (IFRNS) and 11 were frequent relapse steroid dependant nephrotic syndrome (FRNS + SDNS). Bronchial asthma and allergic dermatitis were found in about 63% cases of both steroid resistant nephrotic syndrome (SRNS) and frequent relapse steroid dependant (FRNS+SDNS) group. Hypertension was found in higher number of patient in SRNS compared to SSNS (P> 0.05) It was absent in IFRNS. Steroid contributed more than the disease process in producing hypertension (P< 0.01). Complement C3 comparison among the group could not reach statistically significant level. Similarly, comparison of hematuria showed no difference among the groups but pyuria was higher in SRNS compared to IFRNS (P >0.05). UTI were found equally in all the groups. Conclusion: Higher incidence of asthma, atopic dermatitis were noted in all the groups of idiopathic nephrotic syndrome (INS). C3 was not found significantly low in INS. Persistent elevation of blood pressure is found in higher number of SRNS compared to SSNS and steroid contributed more than the disease process. DOI: http://dx.doi.org/10.3329/bjch.v35i1.10367 BJCH 2011; 35(1): 11-15